Interconnected Forces: Analyzing Urbanization, Economic Growth, Energy Consumption, and Forest Area in the Top 10 Populous Nations’ CO2 Emissions - Pujiati, Amin; Rahman, Yozi Aulia; Kistanti, Nurjannah Rahayu; Nihayah, Annis Nurfitriana; Nabila, Nur Amalia (International Journal of Energy Economics and Policy, 2024)
Economic progress is often seen as a means to enhance living standards, yet it often comes with an unintended consequence: a decline in environmental well-being. This research seeks to validate the Environmental Kuznets Curve (EKC) theory within the top 10 most populous nations and scrutinize the impact of urbanization, economic advancement, energy usage, and forest coverage on CO2 emissions. Utilizing data sourced from the World Development Indicator spanning from 2000 to 2019, this study employed a robust analytical approach known as the generalized method of moments (GMM) dynamic panel data, validated through Sargan and Arellano-Bond tests. The findings affirmed that economic growth, energy consumption, and forest area exerted significant influence on carbon dioxide emissions, aligning with the EKC hypothesis. However, contrary to expectation, urbanization didn't display a discernible impact on emissions, likely due to well-integrated transportation systems and higher educational standards prevalent in urban settings. This underscores the necessity for a sustainable economic growth strategy, advocating for industries with minimal pollution and eco-friendly products conducive to easy recycling. Furthermore, initiatives aimed at expanding forested areas should consider innovative techniques like vertical garden-based reforestation.